PERMASALAHAN PEMBELAJARAN TOLAK PELURU DI SEKOLAH DASAR DAN POTENSI PEMANFAATAN AUGMENTED REALITY BERBASIS BUDAYA LOKAL - Aris Munandar, Ravinda; Rosynanda Nur Fauziah; Mega Sukma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Shot put learning in elementary schools is an integral part of Physical Education that plays an important role in developing basic motor skills, physical strength, and students’ character. However, in practice, shot put learning still faces various challenges, including low student motivation, limited learning media, the dominance of conventional teaching methods, and the lack of integration of local cultural contexts. These conditions make learning less meaningful and difficult for students to understand. This study aimed to identify the problems of shot put learning in elementary schools and to analyze the potential use of Augmented Reality based on local culture as an innovative solution in Physical Education learning. This research employed a descriptive approach using quantitative methods supported by qualitative data obtained from questionnaires, observations, skill tests, and interviews with physical education teachers and students. The findings indicated that shot put learning was still dominated by conventional media, which limited clear and engaging visualization of movement techniques. In addition, local cultural elements had not been optimally integrated into the learning process. The use of Augmented Reality based on local culture has strong potential to enhance learning quality through interactive, contextual, and easily understood three-dimensional movement visualization. This media is also expected to increase students’ learning motivation, active participation, and comprehensive understanding of basic shot put techniques. Therefore, the development of local culture-based Augmented Reality is recommended as a relevant and innovative learning media to support meaningful and contextual Physical Education learning in elementary schools.